Combined precoding for multiuser Multiple-Input Multiple-Output satellite communications. (October 2018) - Ángeles Simarro, M.; Puig, Beatriz; Martínez-Zaldívar, F.J.; Gonzalez, Alberto
Abstract: Applying Multiple-Input Multiple-Output (MIMO) techniques in satellite communications can increase data rates. However, new signal processing elements have to be taken into account to fully exploit the expected advantages of MIMO communications. In this paper, we evaluate different precoding techniques over the satellite channel. A performance comparison between several precoders in terms of Bit Error Rate (BER) and complexity is given for different channel realizations. Furthermore, a novel hybrid scheme for signal precoding is proposed that optimizes the computation for a required BER. The new scheme is based on the matrix condition number of the satellite MIMO channel.